Metformin Potentiates the Effects of Anlotinib in NSCLC via AMPK/mTOR and ROS-Mediated Signaling Pathways - Zhu, Zhongling; Jiang, Teng; Suo, Huirong; Xu, Shan; Zhang, Cai; Ying, Guoguang; Yan, Zhao (Frontiers in Pharmacology, 2021)
Anlotinib is a novel multi-targeted tyrosine kinase inhibitor with activity against soft tissue sarcoma, small cell lung cancer, and non-small cell lung cancer (NSCLC). Potentiating the anticancer effect of anlotinib in combination strategies remains a clinical challenge. Metformin is an oral agent that is used as a first-line therapy for type 2 diabetes. Interesting, metformin also exerts broad anticancer effects through the activation of AMP-activated protein kinase (AMPK) and inhibition of mammalian target of rapamycin (mTOR). Here, we evaluated the possible synergistic effect of anlotinib and metformin in NSCLC cells. The results showed that metformin enhanced the antiproliferative effect of anlotinib. Moreover, anlotinib combined with metformin induced apoptosis and oxidative stress, which was associated with the activation of AMPK and inhibition of mTOR. Reactive oxygen species (ROS)- mediated p38/JNK MAPK and ERK signaling may be involved in the anticancer effects of this combination treatment. Our results show that metformin potentiates the efficacy of anlotinib in vivo by increasing the sensitivity of NSCLC cells to the drug. These data provide a potential rationale for the combination of anlotinib and metformin for the treatment of patients with NSCLC or other cancers.